Pengaruh Kompetensi dan Lingkungan Kerja terhadap Kinerja Pegawai Biro SDM Polres Karawang - Putri, Viranty Herlyna; Karyaningsih, Karyaningsih (J-MAS (Jurnal Manajemen dan Sains), 2024)
Viranty Herlyna Putri, 2023. The influence of competency and work environment on employee performance Biro SDM Polres Karawang. Thesis. Faculty of Economics. University of Singaperbangsa Karawang. In this study, it is related to the influence of competency and work environment on employee performance Biro SDM Polres Karawang. The quantitative method used in this study along with descriptive and verification approaches. Quantitative methods are relied on in this case along with descriptive and verification approaches. The primary data relied on in this case, namely questionnaires and unstructured interviews, non-probability sampling technique is the technique for collecting data for this research. Employees at the Karawang Police HR Bureau are the population in this study, with a total of 59 employees, in determining the sample by relying on saturated sampling, there were 59 employees consisting of Polri and ASN or PNS Polri. The success of this research using Microsoft Word, Microsoft Excel and SPSS 24. In this study, it provides the fact that there is a significant parcial effect on the competence variable of 0,41% and the work environment variable of 44,1% on employee performance at Biro SDM Polres Karawang. Furthermore, there is a simultaneous effect on competence and work environment variables on the performance of Biro SDM Polres Karawang with simultaneous value contribution reaching 74,4% and the remaining 25,6% is contribution of other variables not examined in this study.